Between the sheets: Investigating young adults' communication during sexual activity. Issue 2 (18th June 2020) - Denes, Amanda; Crowley, John P.; Bennett, Margaret
Abstract: The present study investigated young adults' self‐reported communication during sexual activity and its link to sexual and relational outcomes. The associations between two forms of communication during sexual activity (i.e., positive relational disclosures and erotic talk) and orgasm and relationship satisfaction were explored. Additionally, the study tested whether orgasm mediated the association between communication during sexual activity and relationship satisfaction. Three‐hundred and nineteen young adults (237 women, 82 men) ranging in age from 18–32 years ( M = 19) completed a survey within 2 hours of a recent sexual episode addressing their communication during sexual activity. Results revealed that positive relational disclosures, but not erotic talk, predicted the likelihood of orgasm, controlling for participants' biological sex. More specifically, individuals who disclosed more positive feelings during sexual activity were more likely to orgasm. Additionally, the more individuals disclosed positive thoughts and feelings for their partners during sexual activity or the more they engaged in mutualistic erotic talk that included intimacy and bonding, the higher their reported relationship satisfaction after sexual activity. The implications of these findings for research on sexual satisfaction, relational health, and the post sex disclosures model are discussed.